Śahara-dara-śahara umaṛatī hai nadī : (saṃsmaraṇa) - Udbhrānta, 1948- (Dillī : Yaśa Pabliśarsa eṇḍa Ḍisṭrībyūṭarsa, 2017)
Memoirs of Udbhrānta, born 1948, Hindi author about his life, works, and Hindi literature of his times.
In Hindi.
Keywords: Udbhrānta, -- 1948-; Authors, Hindi -- 20th century -- Biography; Hindi literature -- 20th century -- History and criticism; Udbhrānta, -- 1948-; Authors, Hindi; Hindi literature; 1900-1999; Biographies; Criticism, interpretation, etc